The brain’s weakness in the face of trauma: How head trauma causes the destruction of the brain - Johnstone, Daniel M.; Mitrofanis, John; Stone, Jonathan (Frontiers in Neuroscience, 2023)
Of all our organs, the brain is perhaps the best protected from trauma. The skull has evolved to enclose it and, within the skull, the brain floats in a protective bath of cerebrospinal fluid. It is becoming evident, however, that head trauma experienced in young adult life can trigger a degeneration/destruction of the brain, decades later. The level of trauma that induces such delayed destruction is still being assessed but includes levels well below that which cracks the skull or causes unconsciousness or concussion. Clinically this delayed damage appears as dementia, in people who played body-contact sports in their youth or have survived accidents or the blasts of combat; and appear also, we argue, in old age, without a history of head trauma. The dementias have been given different names, including dementia pugilistica (affecting boxers), chronic traumatic encephalopathy (following certain sports, particularly football), traumatic brain injury (following accidents, combat) and Alzheimer's (following decades of life). They share common features of clinical presentation and neuropathology, and this conceptual analysis seeks to identify features common to these forms of brain injury and to identify where in the brain the damage common to them occurs; and how it occurs, despite the protection provided by the skull and cerebrospinal fluid. The analysis suggests that the brain’s weak point in the face trauma is its capillary bed, which is torn by the shock of trauma. This identification in turn allows discussion of ways of delaying, avoiding and even treating these trauma-induced degenerations.